Melatonin treatment protects against spinal cord injury induced functional and biochemical changes in rat urinary bladder - (:unkn) unknown (WILEY, 2012)
Oxidative stress induced by spinal cord injury (SCI) has deleterious effects on the function of several organ systems including the urinary bladder. In this study, we investigated the possible protective actions of melatonin on SCI-induced oxidative damage and urinary bladder dysfunction. Wistar albino rats (n = 24) were divided randomly as control, vehicle- or melatonin (10 mg/kg, ip)-treated SCI groups. To induce SCI, a standard weight-drop method that induced a moderately severe injury at T10 was used. Injured animals were given either vehicle or melatonin 15 min postinjury. One week postinjury, each rat was neurologically examined and then decapitated; blood samples were taken to evaluate neuron-specific enolase (NSE) and soluble protein 100 beta (S-100 beta). Spinal cord (SC) and urinary bladder samples were taken for functional studies and histological examination or stored for the measurement of malondialdehyde (MDA), glutathione (GSH) and nerve growth factor (NGF) levels and caspase-3 activity. Isometric contractions in bladder strips were induced by carbachol. In the SCI rats, decreased contractile responses of the bladder strips were found to be restored by melatonin treatment. Serum S-100 beta levels and NSE activities and tissue MDA levels and caspase-3 activities, all of which were elevated in the vehicle-treated SCI animals as compared to the control values, were reversed by melatonin treatment. On the other hand, reduced GSH and NGF levels due to SCI were restored by melatonin treatment. Furthermore, melatonin treatment improved histological findings. These findings suggest that melatonin reduces SCI-induced tissue injury and improves bladder functions through its effects on oxidative stress and NGF.
Keywords: bladder; caspase-3; nerve growth factor; oxidative stress; spinal cord injury; NERVE GROWTH-FACTOR; FOCAL CEREBRAL-ISCHEMIA; OXIDATIVE STRESS; SUBARACHNOID HEMORRHAGE; LIPID-PEROXIDATION; REACTIVE OXYGEN; S-100 PROTEIN; MESSENGER-RNA; UP-REGULATION; BRAIN-DAMAGE